2021
DOI: 10.29090/psa.2021.03.19.026
|View full text |Cite
|
Sign up to set email alerts
|

Health burden of overweight and obesity: Mortality and years of life lost (YLL) of diseases in Indonesi

Abstract: High prevalence of obesity increased burden from noncommunicable diseases. Our study aimed to estimate the number of death and years of life lost (YLL) diseases related to obesity. The Obesity attributable fraction (OAF) was used to estimate the proportion of each comorbidity attributable to obesity. The number of deaths attributable to obesity was estimated by multiplying the number of patients in each disease category and the OAF. The YLL was calculated by the number of years remaining life and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Susi Ari Kristina and her coauthors have shown that high prevalence of obesity can increase the burden from some non-communicable diseases, such as diabetes type 2, cardiovascular diseases, and cancers (Kristina et al, 2021). In a report, the Health Department of South Africa has that obesity is one of the major public health concerns that are facing South Africa, and its impact and cost extends to individuals, families, communities, the health service, and society as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Susi Ari Kristina and her coauthors have shown that high prevalence of obesity can increase the burden from some non-communicable diseases, such as diabetes type 2, cardiovascular diseases, and cancers (Kristina et al, 2021). In a report, the Health Department of South Africa has that obesity is one of the major public health concerns that are facing South Africa, and its impact and cost extends to individuals, families, communities, the health service, and society as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some unhealthy coping mechanisms binge-eating and social isolation may develop among obese individuals (Dingemans et al, 2002). Certain diseases, such as Cushing syndrome, hypothyroidism, arthritis, Prader-Willi syndrome can cause weight gain (Kristina et al, 2021).…”
Section: Obesity and Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity in Indonesia has increased significantly between 2007 (10.5%) and 2018 (21.8%) [ 4 , 5 ]. There is a growing interest in the genetic predisposition of obesity in Indonesia since mortality due to obesity comorbidities have risen to the nation’s top [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%